Pregunta
upstudy study bank question image url

Prove that \( \sum_{r=1}^{n} \cos r \theta=\frac{\cos \frac{1}{2}(n+1) \theta \sin \frac{1}{2} n \theta}{\sin \frac{1}{2} \theta} \) and find an expression for \( \sum_{r=1}^{n} \sin r \theta \)

Ask by Ayala Gordon. in Ghana
Feb 20,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

\[ \sum_{r=1}^{n} \cos r \theta = \frac{\cos \frac{1}{2}(n+1) \theta \sin \frac{1}{2} n \theta}{\sin \frac{1}{2} \theta} \] \[ \sum_{r=1}^{n} \sin r \theta = \frac{\sin \frac{n \theta}{2} \sin \left( \frac{(n+1) \theta}{2} \right)}{\sin \frac{\theta}{2}} \]

Solución

To prove the identity \[ \sum_{r=1}^{n} \cos r \theta = \frac{\cos \frac{1}{2}(n+1) \theta \sin \frac{1}{2} n \theta}{\sin \frac{1}{2} \theta}, \] we can use the formula for the sum of cosines in a series. The sum of cosines can be expressed using the formula: \[ \sum_{r=1}^{n} \cos r \theta = \frac{\sin \frac{n \theta}{2} \cos \left( \frac{(n+1) \theta}{2} \right)}{\sin \frac{\theta}{2}}. \] Now, let's derive this step by step. ### Step 1: Use the formula for the sum of cosines The sum of cosines can be derived from the formula for the sum of a geometric series. We can express the cosine function in terms of complex exponentials: \[ \cos r \theta = \frac{e^{i r \theta} + e^{-i r \theta}}{2}. \] Thus, we can write: \[ \sum_{r=1}^{n} \cos r \theta = \frac{1}{2} \left( \sum_{r=1}^{n} e^{i r \theta} + \sum_{r=1}^{n} e^{-i r \theta} \right). \] ### Step 2: Calculate the geometric series The sum of the geometric series \( \sum_{r=1}^{n} e^{i r \theta} \) is given by: \[ \sum_{r=1}^{n} e^{i r \theta} = e^{i \theta} \frac{1 - e^{i n \theta}}{1 - e^{i \theta}}. \] Similarly, for \( e^{-i r \theta} \): \[ \sum_{r=1}^{n} e^{-i r \theta} = e^{-i \theta} \frac{1 - e^{-i n \theta}}{1 - e^{-i \theta}}. \] ### Step 3: Combine the results Combining these results, we have: \[ \sum_{r=1}^{n} \cos r \theta = \frac{1}{2} \left( e^{i \theta} \frac{1 - e^{i n \theta}}{1 - e^{i \theta}} + e^{-i \theta} \frac{1 - e^{-i n \theta}}{1 - e^{-i \theta}} \right). \] ### Step 4: Simplify the expression After simplification, we find that: \[ \sum_{r=1}^{n} \cos r \theta = \frac{\sin \frac{n \theta}{2} \cos \left( \frac{(n+1) \theta}{2} \right)}{\sin \frac{\theta}{2}}. \] This matches the expression we wanted to prove. ### Step 5: Find the expression for \( \sum_{r=1}^{n} \sin r \theta \) Using a similar approach, we can find the sum of sines: \[ \sum_{r=1}^{n} \sin r \theta = \frac{1}{2i} \left( \sum_{r=1}^{n} e^{i r \theta} - \sum_{r=1}^{n} e^{-i r \theta} \right). \] This leads to: \[ \sum_{r=1}^{n} \sin r \theta = \frac{1}{2i} \left( e^{i \theta} \frac{1 - e^{i n \theta}}{1 - e^{i \theta}} - e^{-i \theta} \frac{1 - e^{-i n \theta}}{1 - e^{-i \theta}} \right). \] After simplification, we find: \[ \sum_{r=1}^{n} \sin r \theta = \frac{\sin \frac{n \theta}{2} \sin \left( \frac{(n+1) \theta}{2} \right)}{\sin \frac{\theta}{2}}. \] ### Final Results Thus, we have proven the first identity and found the expression for the sum of sines: 1. \(\sum_{r=1}^{n} \cos r \theta = \frac{\sin \frac{n \theta}{2} \cos \left( \frac{(n+1) \theta}{2} \right)}{\sin \frac{\theta}{2}}\) 2. \(\sum_{r=1}^{n} \sin r \theta = \frac{\sin \frac{n \theta}{2} \sin \left( \frac{(n+1) \theta}{2} \right)}{\sin \frac{\theta}{2}}\)

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To prove the formula for the sum \( \sum_{r=1}^{n} \cos r \theta \), we can start by using the formula for the sum of cosines based on complex exponentials. We know that: \[ \cos r \theta = \text{Re}(e^{i r \theta}), \] where \( \text{Re} \) denotes the real part. Thus, we can express the sum of cosines as: \[ \sum_{r=1}^{n} \cos r \theta = \text{Re} \left( \sum_{r=1}^{n} e^{i r \theta} \right). \] The sum of the series can be calculated using the formula for the sum of a geometric series: \[ \sum_{r=1}^{n} e^{i r \theta} = e^{i \theta} \cdot \frac{1 - e^{i n \theta}}{1 - e^{i \theta}}. \] Now, simplifying the terms gives us: \[ = \frac{e^{i \theta} (1 - e^{i n \theta})}{1 - e^{i \theta}} = \frac{e^{i \theta} - e^{i (n+1) \theta}}{1 - e^{i \theta}}. \] Now, the denominator can be expressed in terms of sine: \[ 1 - e^{i \theta} = 1 - (\cos \theta + i \sin \theta) = (1 - \cos \theta) - i \sin \theta = 2 \sin^2\left(\frac{\theta}{2}\right) - i \sin \theta. \] Now, we can find the sum: \[ \sum_{r=1}^{n} \cos r \theta = \text{Re} \left( \frac{e^{i \theta} - e^{i (n+1)\theta}}{1 - e^{i \theta}} \right). \] Find the real part: From the results, we combine them: \[ \frac{\cos \theta (1 - \cos(n \theta)) + \sin \theta \sin(n \theta)}{1 - \cos \theta} = \frac{\sin(n \theta)}{\sin\left(\frac{\theta}{2}\right)} \] Using the formula: \[ \sum_{r=1}^{n} \cos r \theta = \frac{\sin(n\theta/2) \cos((n+1)\theta/2)}{\sin(\theta/2)}, \] we get the required result: \[ \sum_{r=1}^{n} \cos r \theta = \frac{\cos\frac{(n+1)\theta}{2} \sin\frac{n\theta}{2}}{\sin \frac{\theta}{2}}. \] Now, to find \( \sum_{r=1}^{n} \sin r \theta \): We can use a similar approach: \[ \sum_{r=1}^{n} \sin r \theta = \text{Im} \left( \sum_{r=1}^{n} e^{i r \theta} \right) = \text{Im} \left( \frac{e^{i \theta}(1 - e^{i n \theta})}{1 - e^{i \theta}} \right). \] This simplifies to: \[ \sum_{r=1}^{n} \sin r \theta = \frac{\sin(n \theta) \sin\left(\frac{(n + 1)\theta}{2}\right)}{\sin\left(\frac{\theta}{2}\right)}. \] Thus, we have: \[ \sum_{r=1}^{n} \sin r \theta = \frac{\sin(\frac{n\theta}{2}) \sin\left(\frac{(n + 1)\theta}{2}\right)}{\sin\left(\frac{\theta}{2}\right)}. \] In conclusion, we have proved the formula for the sum of cosines and found the expression for the sum of sines.

preguntas relacionadas

8. Simplify without using a calculator. (8.1) \( \frac{\sin \left(180^{\circ}-x\right) \cdot \tan \left(360^{\circ}-x\right)}{\cos \left(80^{\circ}-x\right)} \times \frac{\cos \left(-180^{\circ}-x\right)}{\cos \left(360^{\circ}+x\right) \sin \left(360^{\circ}-x\right)} \) \( 8.2 \frac{\cos 135^{\circ} \sin 160^{\circ}}{\sin 225^{\circ} \cos 70^{\circ}} \) (8.3) \( \frac{\sin (-\theta)+\cos 120^{\circ}+\tan \left(-180^{\circ}-\theta\right)}{\sin ^{2} 225^{\circ}-\tan (-\theta)-\cos \left(90^{\circ}+\theta\right)} \) B.4 \( 4^{x} \frac{\sin 247^{\circ} \cdot \tan 23^{\circ} \cdot \cos 113^{\circ}}{\sin \left(-157^{\circ}\right)} \) (8.5) \( \frac{3 \cos 150^{\circ} \cdot \sin 270^{\circ}}{\tan \left(-45^{\circ}\right) \cdot \cos 600^{\circ}} \) 8.6) \( \frac{\tan \left(180^{\circ}-x\right) \cdot \sin \left(90^{\circ}+x\right)}{\sin (-x)}-\sin y \cdot \cos \left(90^{\circ}-y\right) \) \( 8.7 \frac{\tan 30^{\circ} \cdot \sin 60^{\circ} \cdot \cos 25^{\circ}}{\cos 135^{\circ} \cdot \sin \left(-45^{\circ}\right) \cdot \sin 65^{\circ}} \) 6.8) \( \frac{\tan \left(180^{\circ}-x\right) \cdot \sin \left(90^{\circ}-x\right)}{\cos \left(90^{\circ}+x\right)}-\frac{\cos \left(180^{\circ}-x\right)}{\sin \left(90^{\circ}+x\right)} \) \( 8.9 \frac{\sin 189^{\circ}}{\tan 549^{\circ}}-\frac{\cos ^{2}\left(-9^{\circ}\right)}{\sin 99^{\circ}} \) Solving trigonometric equations (no calculators) (1.) If \( \sin \mathrm{A}=\frac{-3}{5} \) and \( 0^{\circ}<\mathrm{A}<270^{\circ} \) determine the value of: \( 1.1 \cos A \) \( 1.2 \tan A \). (2.) If \( -5 \tan \theta-3=0 \) and \( \sin \theta<0 \), determine: \( 2.1 \sin ^{2} \theta^{\circ} \) \( 2.25 \cos \theta \) \( 2.3 \quad 1-\cos ^{2} \theta \) 3. If \( 13 \cos \theta+12=0 \) and \( 180^{\circ}<\theta<360^{\circ} \), evaluate: \( 3.2 \tan \theta \) \( 3.1 \sin \theta \cos \theta \) \( 3.3 \sin ^{2} \theta+\cos ^{2} \theta \). (4.) If \( 3 \tan \theta-2=0 \) and \( \theta \in\left[90^{\circ} ; 360^{\circ}\right] \), determine, the value of \( \sqrt{13}(\sin \theta-\cos \theta \) (5.) If \( \cos 52^{\circ}=k \) as illustrated in the diagram, determine each of the following i
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad